2010
DOI: 10.1186/1471-2105-11-476
|View full text |Cite
|
Sign up to set email alerts
|

Improving performance of mammalian microRNA target prediction

Abstract: BackgroundMicroRNAs (miRNAs) are single-stranded non-coding RNAs known to regulate a wide range of cellular processes by silencing the gene expression at the protein and/or mRNA levels. Computational prediction of miRNA targets is essential for elucidating the detailed functions of miRNA. However, the prediction specificity and sensitivity of the existing algorithms are still poor to generate meaningful, workable hypotheses for subsequent experimental testing. Constructing a richer and more reliable training d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 31 publications
1
96
0
3
Order By: Relevance
“….,7) in all human and mouse 39 UTR sequences were computed with RNAplfold ) using a window W = 80 and a maximum pairing distance L = 40, as used in other studies Betel et al 2010;Liu et al 2010;Li et al 2011;Vanicek 2011, 2012).…”
Section: Data Sets Of True and False Positivesmentioning
confidence: 99%
See 1 more Smart Citation
“….,7) in all human and mouse 39 UTR sequences were computed with RNAplfold ) using a window W = 80 and a maximum pairing distance L = 40, as used in other studies Betel et al 2010;Liu et al 2010;Li et al 2011;Vanicek 2011, 2012).…”
Section: Data Sets Of True and False Positivesmentioning
confidence: 99%
“…Detailed analyses of proteomics, transcriptomics, and CLIP-seq experiments have confirmed that site accessibility is a useful criterion for discriminating between functional and nonfunctional miRNA binding sites (Hausser et al 2009;Wen et al 2011). Because of its proven role in binding-site identification, accessibility has been employed in several miRNA target prediction methods to reduce the false-discovery rate Muckstein et al 2006;Kertesz et al 2007;Long et al 2007;Busch et al 2008;Betel et al 2010;Liu et al 2010;Vanicek 2011, 2012). Some of these methods have implemented an accessibility filter based on the assumption that only 3-4 nucleotides (nt) in the target should be accessible in order to nucleate the binding with the whole miRNA Long et al 2007;Marin and Vanicek 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The CTS density (site_density) is computed as number_sites/UTR_length, as done in SVMicrO [18]. Finally, another measure of density is computed by counting the maximum number of CTSs that lie within 100 nt of each other (max_100_sites).…”
Section: Other Utr-level Featuresmentioning
confidence: 99%
“…to existing publically available miRNA target prediction software: SVMicrO [18], TargetScan [4], MiRanda [9], RNAhybrid [12], and PITA [13]. Only publically available software is considered in order to obtain predictions on the mock miRNAs.…”
Section: A B C D E F G Hmentioning
confidence: 99%
See 1 more Smart Citation